The early loading of different surface-modified implants: a randomized clinical trial - Kinga Körmöczi; György Komlós; Petra Papócsi; Ferenc Horváth; Árpád Joób-Fancsaly (BMC, 2021)
Abstract Background Various surface treatment options have been adopted with the aim to improve osseointegration, reducing the overall treatment time. Implant stability of early loaded implants with different modified surfaces was compared in the present study. Methods Patients were selected from the Department of Oro-Maxillofacial Surgery and Stomatology at Semmelweis University. Patients randomly received SA (alumina sandblasted and acid-etched), NH (bioabsorbable apatite nanocoating) or SLA (large-grit sandblasted and acid-etched) surface implants. Outcome measures were: implant success, implant stability, and periodontal parameters. The implant stability was measured at the time of implant placement (primary stability) and six weeks after (prothesis delivery, secondary stability). Osstell and Periotest were applied to take all the measurements. The primary and secondary stability were compared in the three study groups Finally the periimplant probing depth appearing after three months of loading was checked on 6 points around to the implant-supported prostheses. Shapiro-Wilk and Mann-Whitney tests were used for the comparison between the study groups. Results A total of 75 implants with different length and diameter were inserted into various positions. One implant failed spontaneously at the fourth week after implant placement. The survival rate was 98,7%. Comparing the primary and secondary stability values, the data were significantly improved in every groups. The difference was the highest in the NH group, however, this difference was not significant compared to the two other groups. Good periodontal parameters were experienced in all the tested implants, independently by the groups. Conclusions With the limitation of the present study, all the implants showed improved stability six weeks after implant placement. A trend of higher result was found for the NH group. Further studies with longer follow-up are needed to confirm this preliminary results. Trial registration: Current Controlled Trials ISRCTN13181677; the date of registration: 04/03/2021. Retrospectively registered.